Modern Technologies and Approaches to Organization of Theoretical and Practical Basic Resuscitation Training for the Lay Public - A. A. Birkun (Неотложная медицинская помощь)
Out-of-hospital cardiac arrest (OHCA) is a serious social and economic problem, and control over it is highly dependent from the overall performance of the system of public first aid and resuscitation training. Coverage of the population with theoretical and practical training in basic cardiopulmonary resuscitation (CPR) is significantly limited in the Russian Federation, and the quality of training is generally low. Based on the analysis of international scientific literature and current international guidelines, this review is delineating modern organizational approaches and technologies of resuscitation training that help to enhance the efficiency and increase the accessibility of CPR training for lay people. In particular, the paper discusses methods of resuscitation training utilizing distant learning technologies, technical means for CPR skills training using feedback and virtual reality technologies, target audience and retraining intervals. Guided by the results of analysis of the cumulative experience, the directions for optimization of the resuscitation training system in Russia are proposed, that offer a perspective to improve coverage of the population with basic CPR training, increase the rates of bystander resuscitation and decrease mortality from OHCA.